Two new species of Paraneseuthia Franz from Okinawa-jima (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2023)
Only one (recently discovered) nominal species of the eutheiine genus Paraneseuthia Franz is known to occur on the largest Ryukyuan Island of Okinawa-jima, while five other members of this rare genus inhabit Ishigaki-jima, Shikoku, Kyushu and Honshu. Undescribed species known from females only have been collected also on southwestern Iriomote-jima and northeastern Hokkaido. Two new Okinawan species are described: P. uminzo sp. n. and P. umisatu sp. n., suggesting that the diversity of Paraneseuthia in the Ryukyus is still known fragmentarily and new discoveries can be expected in other forested southern islands.